1510. Infant Pneumonia and Subsequent Risk of Chronic Respiratory Disorders. (31st December 2020) - Pelton, Stephen I; Lapidot, Rotem; Wasserman, Matthew; Shaff, Melody; Hanau, Ahuva; Lonshteyn, Alexander; Weycker, Derek
Abstract: Background: Community-acquired pneumonia (CAP) in infancy (i.e., among children aged < 2 years) may have long-term consequences for the rapidly developing lung. We examined the impact of pneumonia in infancy on subsequent respiratory health. Methods: A retrospective matched-cohort design and data from Optum's de-identified Integrated Claims-Clinical dataset (2009-2018) were employed. Study population comprised children who were hospitalized for CAP before age 2 years ("CAP patients") as well as matched comparators without evidence of pneumonia before age 2 years ("comparison patients"). CAP patients and comparison patients were matched (fixed 1:5 ratio, without replacement) using estimated propensity scores and a nearest-neighbor approach; those with evidence of selected medical conditions (e.g., extreme prematurity, congenital diseases, respiratory diseases) before age 2 years were excluded. Study outcomes included recurrent pneumonia and a composite of asthma, recurrent wheezing, and hyperactive airway disease. Rates of study outcomes from age 2 to 5 years were estimated for all CAP and comparison patients as well as subgroups of CAP patients (and corresponding comparison patients) stratified by etiology (bacterial, viral, unspecified). Results: Study population totaled 1, 343 CAP patients and 6, 715 comparison patients. CAP patients and comparison patients were well-balanced on their baseline characteristics and mean duration of follow-up was 757 and 729 days, respectively. Rates of chronic respiratory disorders from age 2 to 5 years were significantly higher among CAP patients versus comparison patients. Analyses of subgroups stratified by etiology demonstrated higher rates of study outcomes among CAP patients across all strata. Rates of recurrent pneumonia and a composite of asthma, recurrent wheezing, and hyperactive airway disease from age 2 to 5 years among CAP patients and matched comparison patients Conclusion: Infant CAP foreshadows an increase in subsequent risk of chronic respiratory disorders. Further studies are needed to determine whether this elevated risk is due to infant pneumonia or whether infant pneumonia is a marker of at-risk children. Disclosures: Stephen I. Pelton, MD, Merck vaccine (Consultant, Grant/Research Support)Pfizer (Consultant, Grant/Research Support)Sanofi Pasteur (Consultant, Other Financial or Material Support, DSMB)Seqirus Vaccine Ltd. (Consultant) Rotem Lapidot, MD, MSCI, Pfizer (Consultant) Matthew Wasserman, MSc., Pfizer Inc. (Employee) Melody Shaff, BA, Pfizer, Inc. (Consultant, Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support) Ahuva Hanau, BS, Pfizer, Inc. (Consultant, Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support) Alexander Lonshteyn, PhD, Pfizer, Inc. (Consultant, Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support) Derek Weycker, PhD, Pfizer Inc. (Consultant, Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support)